Unravelling the distinct crystallinity and thermal properties of suberin compounds from Quercus suber and Betula pendula outer barks - Sousa, Andreia F.
The main purpose of this study was to investigate the potential of suberin (a naturally occurring aromatic-aliphatic polyester ubiquitous to the vegetable realm) as a renewable source of chemicals and, in particular, to assess their physical properties. A comparison between cork and birch suberin fragments obtained by conventional depolymerisation processes (hydrolysis or methanolysis) is provided, focusing essentially on their thermal and crystallinity properties. It was found that suberin fragments obtained by the hydrolysis depolymerisation of birch had a high degree of crystallinity, as indicated by their thermal analysis and corroborated by the corresponding XRD diffractions, as opposed to hydrolysis-depolymerised cork suberin counterparts, which were essentially amorphous. (C) 2016 Elsevier B.V. All rights reserved.